2018
DOI: 10.1007/s00438-018-1439-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of Nitrospirillum amazonense strain CBAmC, a nitrogen-fixing bacterium isolated from surface-sterilized sugarcane stems

Abstract: Nitrospirillum amazonense is a nitrogen-fixing bacterium that shows potential to promote plant growth when inoculated into sugarcane and rice plants. This microorganism has been the subject of biochemical and genetic characterization to elucidate important functions related to host plant interaction and growth promotion, including the determination of draft genome sequences of two strains, Y2 and CBAmC, the second of which is the aim of the present study. CBAmC has been isolated from sugarcane (Saccharum spp.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Over the last two decades, while knowledge of associated nitrogen fixation with sugarcane has greatly improved, most of this work focused on specific nitrogen fixing bacteria and lacked a systematic investigation of sugarcane associated communities ( da Silva et al, 2018 ; Singh et al, 2019 ). Recently, with the development of high throughput sequencing technology, the structure and activities of sugarcane microbiome components have been gradually revealed ( Bertalan et al, 2009 ; Pedrosa et al, 2011 ; Sant’Anna et al, 2011 ; Zhu et al, 2012 ; de Souza et al, 2016 ; Yeoh et al, 2016 ; da Silva et al, 2018 ; Dong et al, 2018 ; Schwab et al, 2018 ). In this study, we decipher the composition of a bacterial community in the root and rhizosphere of sugarcane using 16S rDNA sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, while knowledge of associated nitrogen fixation with sugarcane has greatly improved, most of this work focused on specific nitrogen fixing bacteria and lacked a systematic investigation of sugarcane associated communities ( da Silva et al, 2018 ; Singh et al, 2019 ). Recently, with the development of high throughput sequencing technology, the structure and activities of sugarcane microbiome components have been gradually revealed ( Bertalan et al, 2009 ; Pedrosa et al, 2011 ; Sant’Anna et al, 2011 ; Zhu et al, 2012 ; de Souza et al, 2016 ; Yeoh et al, 2016 ; da Silva et al, 2018 ; Dong et al, 2018 ; Schwab et al, 2018 ). In this study, we decipher the composition of a bacterial community in the root and rhizosphere of sugarcane using 16S rDNA sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Although biological nitrogen fixation has been the main explanation for the benefits of inoculation, it is possible that bacteria can stimulate ion absorption and nutrient transport in plants; however, the physiological explanation of the bacterial mixture is still little understood (SCHWAB;TERRA;BALDANI, 2018;SANTOS et al, 2019). Reis Junior et al (2008) found no increase in nitrogen accumulation by maize plants after inoculation with Azospirillum amazonensis.…”
Section: Resultsmentioning
confidence: 99%
“…The association encountered is among fungi ( Barbatospora ambicaudata and Xylaria sp.) and nitrogen-fixing bacteria [ Azospirillum, ( Steenhoudt and Vanderleyden, 2000 ) and Nitrospirillum amazonense ( Schwab et al, 2018 )]. Nitrogen availability in deadwood is highly restricted, therefore fungi may take advantage from associations with nitrogen-fixing bacteria for their growth ( Gómez-Brandón et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%